Comparing human pediatric immune responses to primary infection with dengue, chikungunya and Zika viruses - Tomalin, Lewis E; Bos, Sandra; Fenutria, Rafael; Chen, Yitong; Kim-Schulze, Seunghee; Rahman, Adeeb H; Balmaseda, Angel; Fernandez-Sesma, Ana; Harris, Eva; Suaréz-Fariñas, Mayte (Frontiers in Immunology, 2025)
BackgroundThe four dengue virus serotypes (DENV1-4), Zika virus (ZIKV) and chikungunya virus (CHIKV) have similar epidemiology and transmission cycles and are the most prevalent arthropod-borne viruses in humans, with half the world’s population at risk of infection. Although these infections share overlapping clinical presentations, the immune mechanisms that distinguish these infections, particularly in children, remain poorly defined. We aimed to characterize the immune responses to DENV, ZIKV, and CHIKV in a pediatric population and to define the specific immune signatures associated with each virus.MethodsWe characterized the immune responses to DENV, ZIKV and CHIKV by measuring cytokine/chemokine/growth-factor profiles in plasma/serum samples, and immune-cell profiles in peripheral blood mononuclear cells, collected from children during acute (~1–3 and ~4-6 days) primary infection with DENV1/DENV3 (n=32), ZIKV (n=50) or CHIKV (n=45), and during infection recovery (~14–25 days). ResultsThe innate immune responses to CHIKV and DENV were similar in terms of acute cytokine concentrations and monocyte frequencies. The innate immune response to ZIKV was mild, and the adaptive response was delayed, showing much lower concentrations of inflammatory cytokines and delayed T cell/B cell activation. Overall, the immune response to CHIKV and DENV were most similar than DENV and ZIKV, despite DENV and ZIKV belonging to the same flavivirus genus. The immune response to ZIKV was the most distinct, showing rapid B cell expansion but attenuated/delayed B cell activation. ConclusionThese findings reveal that early immune responses to arboviruses are defined more by infection-specific dynamics than by viral taxonomy, underscoring distinct immunological signatures for each virus.